The Functional Outcome of Normal or High Blood Pressure in Patients with Chronic Glomerulonephritis and Nephrotic Syndrome is Dependent on Association with Functional, Histologic and, Proteinuric Parameters (Global Journal of Medical Research, 2022)
Background: Normal (BP0)or high blood pressure (BP1)are variably present in patients with chronic glomerulonephritis (GN) and Nephrotic Syndrome (NS). At biopsy each BP0 or BP1 patient is associated with different values of renal function, urinary proteins excretion and renal lesions severity [GGS%, TID and AH score]. Thus outcome of BP0 and BP1 may be dependent inevry patient on the associations with these parameters and by eventual treatments with immunosuppressive agents. Methods: In 151 patients with GN and NS the outcome was evaluated in BP0 and BP1 patients according to eGFR#x2265; or lt;60 ml/min/1.73 m2. In 140 patients with renal biopsy performed at the same time of all parameters the outcome was evaluated for 3 types of renal lesions severity (GGS%, TID score and AH score) and according to 4 groups of combined urinary excretion of IgG/C and #x3B1;2m/C. The treatment with steroids and cyclophosphamide was evaluated.